PEMROGRAMAN DINAMIK: ANALISA JARINGAN MENGGUNAKAN PROSEDUR PERT DAN AHP DALAM PENYELESAIAN PERMASALAHAN EKONOMI PERTAHANAN - Endro Tri Susdarwono (CV. Amerta Media, 2020)
Dynamic programming uses mathematical formulation, but there is no standard and systematic procedure to determine the optimal decision. The mathematical equation used is very dependent on the problem at hand. Most importantly, mathematical equations that are built can be an embodiment of the solution to the problem. This is the essence of dynamic programming, which is widely used in various fields such as economic, social, and defense. The use of networks involves various activities that are interconnected, both directly and indirectly. In practice, there are many network analysis models, one of the well-known network models that is used in planning, scheduling, and monitoring is the Program Evaluation and Review Technique (PERT). Analytical Hierarchy Process (AHP) analytic hierarchy process is a decision-making technique developed in cases that have various levels (hierarchy) of analysis. This method uses pairwise comparisons, calculating weighting factors, and analyzing them to produce relative priority among alternatives.Key Words: AHP; Defense Economy; Dynamic programming; PERT